Diseño de una galería de transporte, con la finalidad de conectar el nivel dos del bloque de explotación de la veta oro sol, con el nivel uno, del Área Minera Renacer m3, código 101602, sector San Gerardo, provincia del Azuay. - Jiménez Jiménez, William Alberto (2020)
Mining has become in recent years as one of the strategic sectors for the development of the country, aimed at increasing the economy produced in the mining sector. In the southern region of the country, a number of metallic, non-metallic mineral deposits and natural deposits of construction materials (aggregates and stone) are located, which are sometimes exploited in anti-technical ways damaging the social-environmental environment in which develops. The Ponce Enríquez mining district becomes one of the three most important districts in Ecuador, just like Nambija in the province of Zamora and Zaruma - Portovelo in the province of El Oro, this has led to an important investment in terms of technology and studies that have allowed a development of this industry in the sector. In accordance with the above and due to the need to influence the development of responsible mining in conjunction with the mining owner, the theme has been proposed: “DESIGN OF A TRANSPORT GALLERY, WITH THE PURPOSE OF CONNECTING LEVEL TWO OF THE VETA ORO SOL EXPLOITATION BLOCK, WITH LEVEL ONE, OF THE RENACER M3 MINING AREA, CODE 101602, SAN GERARDO SECTOR, AZUAY PROVINCE”, the area is in the exploitation phase, through a level called two, the same as at the moment it fulfills the functions of the main transport gallery, which for the lower level complicates in terms of productivity and efficiency, hence the need to cross a gallery that meets these functions and the mineral can be transported to the top.